Are anterior urethral valve and anterior urethral diverticulum two separate entities: A radiological and endoscopic review. Issue 1 (February 2021) - Jain, Prashant; Prasad, Ashish; Jain, Sarika
Summary: Background: Anterior urethral valve (AUV) and anterior urethral diverticulum (AUD) are two rare causes of anterior urethral obstruction with variable presentation and anatomy. Their existence as the same or different entity is still debatable, and management has not yet been standardized. Objective: This study is a retrospective review of cases diagnosed with anterior urethral obstruction and correlation of radiological and endoscopic anatomy of AUV and AUD. Study design: A retrospective review of cases diagnosed with AUV and AUD, between May 2013 and February 2020 is presented. The presentation, laboratory, radiological and endoscopic anatomy along with the management required was reviewed. A special emphasis has been given on the correlation of radiological and endoscopic anatomy and an attempt has been made to standardize the management. Results: A total of 8 patients with age ranging from 2 months to 9 years were reviewed. Poor urinary stream and recurrent UTI was the commonest presentation. The anatomy of the anterior urethra on VCUG (voiding cystourethrogram) and Urethrocystoscopy was correlated. Two sets of patients were identified. In the first set, five cases on endoscopy had findings of the classical valve-like fold in the anterior urethra with immediate proximal dilation of the urethra giving the appearance of a 'pseudodiverticula' without any definite opening. In three of these cases, endoscopic findings correlated well with radiological findings of 'pseudodiverticula' in which dilated proximal urethra formed an obtuse angle with the ventral floor of the urethra. The other set of four patients had a 'true diverticula' on endoscopy with a well-defined mouth and prominent distal lip, correlating well with radiological findings of a 'true diverticula' forming an acute angle with the ventral floor of the urethra. One case on endoscopy had both an anterior urethral valve with a proximal 'pseudodiverticula and a large wide-mouthed bulbar 'true diverticula'. All the patients with classical valves were successfully treated using a resectoscope while two patients with 'true diverticula' were successfully managed by incising the distal lip. One of the patients previously managed for the posterior urethral valve (PUV) had both classical valves in the anterior urethra with proximal 'pseudodiverticula' and a bulbar 'true diverticula'. The AUV was ablated with a resectoscope while 'true diverticula' required diverticulectomy. All the patients after follow up of 3 months–8 years, were asymptomatic except the one with 'true diverticulum' who remained symptomatic after TUR (Trans-urethral resection) and required vesicostomy. Discussion: AUV and AUD both can cause obstructive uropathy. The proximal dilatation related to AUV cannot be labeled as a 'true diverticula', which lacks a classical orifice. The distal obstructing lip of 'true diverticula' should not be confused with a classical mucosal valve-like fold seen in AUV. While AUV and small AUD can be treated with endoscopic ablation, large diverticula as a result of wide spongiosal defects require surgical excision. A good understanding of their radiological and endoscopic anatomy is required to differentiate them and decide for appropriate management. Conclusion: Based on our experience, AUV and AUD should be differentiated and should be considered as two separate entities. Summary Figure Schematic diagram showing differences between AUV and AUD based on imaging and endoscopic findings: AUV is an obstructing mucosal valve causing proximal dilatation of the urethra forming a 'pseudodiverticulum', while AUD is a 'true diverticulum' as a result of spongiosal defect with a definite orifice in endoscopy and obstructing distal lip, forming an acute angle with the urethra in VCUG. Summary Figure